Visit Nepal Year 2020: Some Imperatives - Pandey, Rashmi; Dhakal, Rebat Kumar (Social Inquiry: Journal of Social Science Research, 2019)
Tourism is one of the fastest-growing socio-economic sectors of our times. It is also one of the linchpins of Nepalese economy. The purpose of this paper is to overview the tourism development trend in general, and Visit Nepal 2020 in particular, and discuss some ideas which are helpful in addressing current needs of tourism development in Nepal, and also serving as an asset base for future interventions. In this paper, we first analyse the tourism development trend, both global and national, to present the tourism scenario we have thus far created, and, setting aside the preparations done so far for undertaking soon-to-be-launched Visit Nepal year, discuss a few management thoughts which have strategic importance in making the tourism year more effective. This call-to-action paper offers a range of last-minute pointers for tourism policymakers and practitioners, in the context of effecting Visit Nepal 2020, that are more likely to impact and, to some extent, guide the future directions of the tourism industry in Nepal.